The burden and epidemiology of orofacial clefts in Iran from 1990 to 2023: a Global Burden of Disease study with subnational socio-demographic index analysis - Reza Sharifi; Seyed Aria Nejadghaderi; Farnoosh Mohammadi; Mohammad Javad Kharazifard; Zeinab Bakhtiari (PLoS ONE, 2026)
Background Orofacial clefts (OFCs) are among the most frequent congenital craniofacial malformations worldwide. These conditions impose lifelong functional, psychological, and socioeconomic burdens. In Iran, despite several hospital-based and regional studies, an updated national and subnational assessment of OFC burden has been lacking. This study aimed to estimate the incidence, prevalence, disability-adjusted life years (DALYs), and mortality attributable to OFCs in Iran and its 31 provinces from 1990 to 2023, and to explore their associations with the sociodemographic index (SDI). Methods Data were obtained from the Global Burden of Disease (GBD) Study 2023. OFCs were defined according to ICD-10 codes Q35–Q37. GBD modeled estimates were generated using the DisMod-MR 2.1 meta-regression framework. The DisMod-MR 2.1 meta-regression model was applied to derive estimates of metrics. Rates were age-standardized per 100,000 population, and 95% uncertainty intervals (UIs) were calculated. The relationship between OFC burden and SDI was assessed descriptively using smoothing splines models. Results In 2023, Iran recorded 1,208.9 (917.1–1,581.4) new OFC cases, corresponding to an age-standardized incidence rate of 2.5 per 100,000. Prevalence reached 77.3 (62.3–94.7) per 100,000, and DALYs were 6.9 (4.1–10.5) per 100,000. Since 1990, DALY and mortality rates decreased by 88.8% and 96.1%, respectively, while prevalence remained largely stable. The highest prevalence was seen in Tehran (108.3 per 100,000) and the lowest in Isfahan (49.1 per 100,000). The greatest DALY burden occurred among children under five years. There was a negative relationship between SDI and DALY rates. Conclusions The national burden of OFCs in Iran has substantially declined over the past three decades. These findings highlight the need for sustained efforts to improve cleft prevention, early detection, and access to specialized care to further reduce the burden and promote health equity across Iran.